Configurations of Vision in Korean Postwar Poetry: Cases of Jeon Bong-geon and Kim Gu-yong - Jang, Seongho (International Journal of Korean Humanities and Social Sciences, 2025)
This article theorizes the configurations of vision that structure Korean postwar poetry of the 1950s, arguing that war reconfigures visuality itself rather than merely supplying new themes. Building on debates about scopic regimes and modernity’s privileging of vision, I read the Korean War (한국전쟁) as a historical apparatus that reassigns who sees, how seeing is mediated, and what becomes visible or illegible. Through close readings of Jeon Bong-geon (전봉건) and Kim Gu-yong (김구용) – two poets who crystallize the field’s “reality” and “fantastic” currents – I show that vision is neither neutral nor strictly mimetic; it is produced at the intersection of body, weapon, terrain, and trauma. The article contributes a vocabulary for analyzing vision as a historical form in Korean poetry, clarifying how war’s technologies and affects configure what can be seen and said, and why postwar poetry often oscillates between documentary witness and the fantastic.